Clarín y el mundo clásico - Ruiz Pérez, Ángel (1997)
In this paper, the writer Leopoldo Alas, known currently as «Clarín», is considered from the perspective of the history of the classical philology in Spain.
Keywords: Alas, Leopoldo, -- 1852-1901; Humanismo